(untitled) (Bangladesh Journal of Botany, 2020)
A vulnerability assessment index system and model for oasis agriculture to sandstorm disaster had been constructed. The concept was based on the characteristics of oasis agriculture, from the view of comprehensive disaster reduction and regional sustainable development. Seven main oasis agricultural regions in Xinjiang, China in 1980s, 1990s and 2000s were considered. Focusing on the sensitivity of regional hazard formative environments and the adaptability of sandstorm disaster affected bodies, the vulnerability of oasis agriculture was assessed. The results showed that the vulnerability of oasis agriculture to sandstorm disaster changes in different periods and is mainly affected by sensitivity of climate and adaptability of local agricultural conditions. During the past three decades, the sensitivity has been enhanced in some regions, but the vulnerability of the region has not been significantly reduced because of the enhancement of human adaptability.